2010
DOI: 10.1371/journal.pone.0010626
|View full text |Cite
|
Sign up to set email alerts
|

Effective Melanoma Immunotherapy in Mice by the Skin-Depigmenting Agent Monobenzone and the Adjuvants Imiquimod and CpG

Abstract: BackgroundPresently melanoma still lacks adequate treatment options for metastatic disease. While melanoma is exceptionally challenging to standard regimens, it is suited for treatment with immunotherapy based on its immunogenicity. Since treatment-related skin depigmentation is considered a favourable prognostic sign during melanoma intervention, we here aimed at the reverse approach of directly inducing vitiligo as a shortcut to effective anti-melanoma immunity.Methodology and Principal FindingsWe developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 46 publications
2
45
2
Order By: Relevance
“…While our studies investigate CD8 T cell-mediated vitiligo induced by melanoma, in the future it would be interesting to determine if these findings extend to other models of melanocyte destruction (e.g. vitiligo initiated by melanocytoxic chemicals (26, 27), monoclonal antibodies (28), or pathogenic CD4 T cells(29)).…”
Section: Discussionmentioning
confidence: 92%
“…While our studies investigate CD8 T cell-mediated vitiligo induced by melanoma, in the future it would be interesting to determine if these findings extend to other models of melanocyte destruction (e.g. vitiligo initiated by melanocytoxic chemicals (26, 27), monoclonal antibodies (28), or pathogenic CD4 T cells(29)).…”
Section: Discussionmentioning
confidence: 92%
“…We demonstrated that monobenzoneinduced depigmentation on non-exposed locations and drugexposed sites, indicating a systemic immune reaction to autologous melanocytes. The effect of monobenzone on promoting melanocyte antigen-specific immune response has been suggested by the fact that monobenzone and adjuvants imiquimod and CpG promptly suppressed melanoma growth in mice (13). Monobenzone can form quinone-haptens to the tyrosinase which in turn increase melanocyte cell immunogenicity (14).…”
Section: Discussionmentioning
confidence: 99%
“…The idea that melanocyte death drives CD8 + T cell responses to melanoma is supported by published reports that the targeted killing of melanocytes with cytotoxic vectors (36,37), or the melanocytotoxic chemical monobenzone (38), primes robust and long-lived T cell immunity to B16 melanoma. The present studies demonstrate that such stimuli are provided naturally to memory T cells in hosts with vitiligo.…”
Section: Figurementioning
confidence: 98%